G2/M arrest and mitotic slippage induced by fenbendazole in canine melanoma cells. Issue 3 (12th January 2022) - Kim, Sehoon; Perera, Shashini Kanchanamala; Choi, Seo‐In; Rebhun, Robert B.; Seo, Kyoung‐won
Abstract: Background: The use of fenbendazole (FBZ) in terminal cancer patients has recently increased, as anthelminthic drugs, such as FBZ and benzimidazole, exhibit anti‐tubulin effects in tumour cells. Objectives: The present study evaluated the in vitro anti‐cancer effects of FBZ in five canine melanoma cell lines originating from the oral cavity (UCDK9M3, UCDK9M4, UCDK9M5, KMeC and LMeC). Methods: Five canine melanoma cell lines were treated with FBZ and analysed with cell viability assay, cell cycle analysis, western blot assay and immunofluorescence staining to identify apoptotic effect, cell cycle arrest, microtubule disruption and mitotic slippage. Results: Cell viability was reduced in all melanoma cell lines in a dose‐dependent manner after FBZ treatment. Through cell cycle analysis, G2/M arrest and mitotic slippage were identified, which showed a time‐dependent change. All treatment concentrations induced increased cleaved PARP signals in western blot analysis compared to the control groups. Immunofluorescence of cells treated for 24 h revealed defects in microtubule structure, multinucleation or macronucleation. With the exception of UCDK9M3, the melanoma cells showed mitotic slippage and post‐slippage death, indicative of mitotic catastrophe. Conclusions: These results indicate that FBZ exhibits anti‐cancer effects in vitro against canine melanoma cells; however, further in vivo studies regarding the clinical applications of FBZ are required.